2010
DOI: 10.1007/s00431-010-1157-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma isoprostane is associated with visceral fat, high molecular weight adiponectin, and metabolic complications in obese children

Abstract: Oxidative stress is considered to be increased in obese subjects. However, the association of oxidative stress with visceral adiposity and adiponectin level is not fully understood in children. Forty-four obese Japanese children and adolescents, 28 boys and 16 girls, with median age of 9.9 years [5.2-13.8 years], and the 28 age-matched non-obese healthy controls, 15 boys and 13 girls, were enrolled in this study. The median BMI Z scores were +2.21 [1.31-4.38] for the obese subjects and -0.72 [-2.11-1.31] for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 35 publications
(56 reference statements)
4
32
0
1
Order By: Relevance
“…Despite the differences in anthropometric and biochemical variables between obese and controls in the larger population were, somehow, maintained, no significant changes were observed between the two groups regarding TA and absolute and relative multimers concentrations, both before and after the PE program (data not shown). Oppositely, some studies have pointed to an increase in HMW following intervention (16,24). The lack of significant differences might be related to a small sample size, however, it can also indicate that the differences previously found could be due to confounding factors, present later in life, or, that differences in TA concentrations seen at older ages, might be caused by a cumulative effect, still not evident at early ages.…”
Section: Analysis Of Adiponectin Multimersmentioning
confidence: 91%
See 1 more Smart Citation
“…Despite the differences in anthropometric and biochemical variables between obese and controls in the larger population were, somehow, maintained, no significant changes were observed between the two groups regarding TA and absolute and relative multimers concentrations, both before and after the PE program (data not shown). Oppositely, some studies have pointed to an increase in HMW following intervention (16,24). The lack of significant differences might be related to a small sample size, however, it can also indicate that the differences previously found could be due to confounding factors, present later in life, or, that differences in TA concentrations seen at older ages, might be caused by a cumulative effect, still not evident at early ages.…”
Section: Analysis Of Adiponectin Multimersmentioning
confidence: 91%
“…Other studies have reported that BMIzsc reduction is related to an increase in TA, particularly in the HMW form (16,24). In children, adiponectin decreases with aging (6); therefore, a small reduction of BMIzsc (0.2), might not be enough to raise the TA levels, but it seems to be enough to slow the process as age-related adiponectin reduction seems to be accelerated in obese individuals.…”
Section: Exercise Adiponectin and Metabolismmentioning
confidence: 99%
“…Also, addition of chemerin to cultured endothelial cells upregulated the expression of adhesion molecules for white blood cells. Additionally, both childhood obesity and inflammation lead to oxidative stress (45)(46)(47), since they induce the generation of reactive oxygen species and lower the anti-oxidant capacity.…”
Section: Review Bruyndonckx Et Almentioning
confidence: 99%
“…In addition, a lower dietary intake of α-tocopherol and β-carotene in humans increases the oxidative stress status [13]. Previous studies have also indicated that plasma levels of 8-isoprostane are significantly correlated with visceral fat area rather than subcutaneous one [2,35]. Ito et al [15] reported that the C/EBPβ up-regulates the expression of inflammatory mediator adipokines, such as MCP-1 and IL-6.…”
mentioning
confidence: 99%
“…Obese subjects have higher levels of oxidative stress biomarkers, such as 8-isoprostane, than their leaner counterparts. 8-isoprostane is an eicosanoid produced by the random oxidation of lipids by oxygen radicals, and its plasma levels accurately reflect the oxidative stress status in obese patients [2,35,36]. On the other hand, previous reports have indicated that dietary supplementation with α-tocopherol, the most potent antioxidant component among vitamin E, reduced oxidative stress with the reduction of plasma 8-isoprostane concentrations in obese patients [17,37,38].…”
mentioning
confidence: 99%